Answer:
[tex]f(3)=7[/tex]
Step-by-step explanation:
Given:
[tex]x[/tex] [tex]f(x)[/tex]
0 -2
2 4
6 16
Let us first determine whether the rate of change of the function is constant or not.
The rate of change of the function is given as:
[tex]m=\frac{f(x_2)-f(x_1)}{x_2-x_1}[/tex]
So, for [tex]x_1=0,f(0)=-2,x_2=2,f(2)=4[/tex]
[tex]m=\frac{4-(-2)}{2-0}=\frac{4+2}{2}=\frac{6}{2}=3[/tex]
For the next set of numbers, [tex]x_2 = 2, f(2)=4,x_3=6,f(6)=16[/tex]
[tex]m=\frac{16-4}{6-2}=\frac{12}{4}=3[/tex]
Therefore, the rate of change of the function is a constant. Therefore, the relationship is a linear relationship.
A linear relationship with a given point [tex](x_1,y_1)[/tex] and constant rate of change [tex]m[/tex] is given as:
[tex]y-y_1=m(x-x_1)\\y-(-2)=3(x-0)\\y+2=3x\\y=3x-2\\\therefore f(x)=3x-2[/tex]
Now, value of [tex]f(3)[/tex] is obtained by plugging in 3 for [tex]x[/tex] in the above expression.
[tex]f(3)=3(3)-2\\f(3)=9-2=7[/tex]